Proyecto de factibilidad para la importación y comercialización de llantas para vehículos livianos en la provincia de Los Ríos - García Arévalo, Wellington Manuel (2015)
The present research had as main objective PREPARE THE PROJECT FEASIBILITY FOR IMPORT AND MARKETING OF TIRES FOR LIGHT VEHICLES IN THE PROVINCE OF RIVERS, To meet this goal was necessary to use the scientific, deductive, analytical, inductive methods , statistical and techniques that the survey applied to establish the demand and supply of the product to demand a sample of 398 surveys were applied and to determine the offer were applied at 2 distributors of this product in the province of Los Ríos applied With these data it was possible to establish the potential demand was 78.255 vehicles; the actual demand was 43,257 vehicles, then use per capita was estimated at 4 tires tires average annual per vehicle, allowing determine the effective demand in 123,542; 11412 total supply in tires, unsatisfied demand was 112,130 tires for the first year of life of the project. The technical study installed in 7640 tire capacity is determined, working at 80% for the first year ie 6112 tires, the administrative work is to establish that the company is legally conform as a limited liability company, establishing the positions of Manager, Secretary Accountant, Sales Manager Sales Driver & Guardian, and finally the financial study discloses the total investment of $ 59,564.41, the same as 58% financed by investors and 42% with credit Bank Promoting a 5 year term and financial indicators which determine the feasibility of it was calculated; total costs for the first year is $ 48,253.22, which determines a unit cost of $ 73.35 per tire, with a profit margin of 15% giving a total revenue of $ 448,294.53 The financial evaluation, the NPV was a positive value 153,129.43, the IRR is 50.51%, capital recovery will be in 2 years 10 months and 12 days, the benefit cost worth 0.15 cents for every dollar invested is obtained, analysis sensitivity shows that the project supports 6.98% increase in costs and 6.06% in reducing their income. The most important conclusion was that demonstrates that the implementation of the investment project is feasible, and the recommendation is implemented this project